Facile preparation of pyrimidinediones and thioacrylamides via reductive functionalization of amides. Issue 65 (2nd August 2017) - Trillo, Paz; Slagbrand, Tove; Tinnis, Fredrik; Adolfsson, Hans
Abstract : A protocol for the mild and chemoselective reductive functionalization of amides into pyrimidinediones and thioacrylamides has been developed. Abstract : The development of an efficient protocol for the reductive functionalization of amides into pyrimidinediones and amino-substituted thioacrylamides is presented. Enamines are generated in a highly chemoselective amide hydrosilylation reaction catalyzed by molybdenum hexacarbonyl in combination with 1, 1, 3, 3-tetramethyldisiloxane. The direct addition of either isocyanate or isothiocyanate generates the corresponding pyrimidinediones and 3-aminothioacrylamides in high yields.